Implementation of Interactive Books Based on Local Wisdom and STEAM as Creative Learning in Islamic Early Childhood Education - Qomariah, Choirul; Yulia, Nikmahtul Khoir Tri (PIAUD Universitas Islam Negeri Sunan Kudus, 2023)
This research aims to investigate the implementation of interactive books based on local wisdom and STEAM as a creative learning tool in Islamic Early Childhood Education, through a case study method. The study was conducted at KB-TA Amanah Bunda Lawang, Malang, focusing on the local wisdom of East Javanese language and the theme of creating traditional toys for children. Data were obtained through observations, where 80% of the students were observed learning through interactive books using the STEAM approach, and 90% of the students actively engaged in creating loose part toys after the book was read. Furthermore, feedback from the students and teachers indicated that there is a need to synchronize the illustrations and text in the STEAM interactive book. These findings provide valuable insights into the effectiveness and further development needs regarding the implementation of interactive books based on local wisdom and STEAM in KB-TA Amanah Bunda Lawang. The research recommendations include the development of more visually integrated and culturally relevant STEAM interactive books, as well as the use of teaching methods that support children's creativity and active participation.